STRATEGI BERTAHAN OJEK SEBAGAI SARANA TRANSPORTASI DI LIMAU MANIS KECAMATAN PAUH KOTA PADANG - Naldi, Hendra; Prahara, Surya; Firdaus, Firdaus (Pendidikan Sosiologi, 2014)
Transportation is important tool in economy acountry. The transportation needed highest because part of the society to stay in country donât have transportation, so alternative transportation be solution for the society as motorcycle used for public transportation or angkot. The research purpose is to describe about factor that reason for the society to choose more motorcycle used for public transportation in Limau Manis Pauh Kota Padang regency, for describe what the motivation motorcycle used for public transportation people to become motorcycle used for public transportation in Limau Manis Pauh Kota Padang regency and describe how the motorcycle used for public transportation peopleâs strategy to keep the passengers in Limau Manis Pauh Kota Padang regency. The research use of theory social measure to according by Max Weber. The research use kualitative approach with use the research type descriptive. The research use the technique of purpose sampling. This research use primary and secondary data. The technique for in the research is observation, review, documentation, techniques, all of the data. To get from the analysis with reducation data, display data, and summarize data. The result of research 1) Factor as motivate the society to choose motorcycle used for public transportation as transportation it cause, first, effective and efficient (time of efficient, the purpose of efficient, and power efficient) second, practices. 2) To motivate the motorcycle used for public transportation people, first, to make the family needed. Second, the highest income. 3) The motorcycle used for public transportation strategies to keep the passenger, first, the good relation second, to costume the passenger friendly.